Efektivitas Latihan Fartlek dalam Meningkatkan Kapasitas VO2MAX - Fajrin, Muhammad Nur; BS, Nurul Ainun; Rusli, Muhammad Apriliyansyah Pratama; Azrah, Nurhikmah; Rustan, Muhammad Iqbal; Rusadi, Rahmat Agung; Irvan; Arfanda, Poppy Elisano (Lembaga Intelektual Muda (LIM) Maluku, 2026)
This study is a quantitative research aimed at determining the effect of fartlek training on the improvement of VO2Max endurance in PPLP/SKO Sulawesi Selatan athletes. The type of research used is an experiment with the independent variable being fartlek training and the dependent variable being the improvement in maximum oxygen volume (VO2Max). The population in this study consisted of all PPLP/SKO Sulawesi Selatan athletes, with a sample size of 25 people. Data collection techniques were carried out through tests and observation sheets, while data analysis used descriptive statistics and t-tests using the SPSS version 20.00 program. The results of the t-test showed a t-value of 11.195, which was greater than the t-table value of 1.71088 () with a significance value of . Based on these results, it can be concluded that there is a significant effect of Fartlek training on increasing VO2Max endurance in PPLP/SKO Sulawesi Selatan athletes.